1997
DOI: 10.1093/oxfordjournals.aje.a009326
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Relation between Endogenous Testosterone and Cardiovascular Disease Risk Factors in Middle-aged Men: A 13-Year Follow-up of Former Multiple Risk Factor Intervention Trial Participants

Abstract: The present study examined lifestyle and behavioral correlates of the change in total testosterone over 13 years in 66 men aged 41-61 years who were former participants of the Multiple Risk Factor Intervention Trial (MRFIT) at the Pittsburgh, Pennsylvania, center. The authors also determined in these men if changes in total testosterone are related to changes in cardiovascular disease risk factors. The mean total testosterone level was 751 (standard deviation, 248) ng/dl at baseline and decreased by 41 (standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
174
5
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 330 publications
(200 citation statements)
references
References 58 publications
16
174
5
5
Order By: Relevance
“…It has been hypothesized that parental hormone concentrations around the time of conception might determine the sex of the child to some extent, low concentrations of testosterone and estrogen being associated with the birth of girls [24]. Some studies have suggested that smoking reduces estrogen levels in women and testosterone levels in men [25,26]. On the basis of these arguments, we would have expected to find a lower male:female ratio among the patients' children.…”
Section: Discussionmentioning
confidence: 98%
“…It has been hypothesized that parental hormone concentrations around the time of conception might determine the sex of the child to some extent, low concentrations of testosterone and estrogen being associated with the birth of girls [24]. Some studies have suggested that smoking reduces estrogen levels in women and testosterone levels in men [25,26]. On the basis of these arguments, we would have expected to find a lower male:female ratio among the patients' children.…”
Section: Discussionmentioning
confidence: 98%
“…The significance of our findings has to be judged in the light of the conflicting knowledge concerning testosterone and cardiovascular risk factors suggesting several roles of androgens of both direct and indirect nature. Low testosterone concentrations could have an adverse effect on body composition [7,8,9,10,51] and haemostatic parameters, such as plasminogen-activator-inhibitor type 1 [52,53]. In men, low concentrations of endogenous testosterone were found to be associated with reduced concentrations of HDL cholesterol while exogenous androgens, including testosterone, decrease HDL cholesterol [8,11,25,54,55,56].…”
Section: Discussionmentioning
confidence: 99%
“…As early as 50-60 years ago it was realized that aging is accompanied by significant reduction in testosterone levels [97,98]. Although some follow-up studies failed to detect age-related decline in plasma testosterone levels in older men [99][100][101][102][103][104], subsequent population-based cross-sectional and longitudinal studies have confirmed progressive loss of testosterone with aging in healthy men [96,[105][106][107][108][109][110][111][112][113][114][115][116][117][118][119][120][121][122]. Mirroring this decline in plasma testosterone concentration is an age associated increase in sex-hormonebinding globulin (SHBG) level [117], a major plasma carrier of testosterone, resulting in even more dramatic decreases in unbound free testosterone [110,[123][124][125], and weakly bound bioavailable testosterone [126,127].…”
Section: Humansmentioning
confidence: 99%